Off-target effects and adverse outcomes of fibroblast growth factor 23 in chronic kidney disease - Di Marco,Giovana S (2018)
Chronic kidney disease (CKD) patients have a high risk of death, especially cardiovascular death. High fibroblast growth factor 23 (FGF23) levels are independently associated with higher risk of death and cardiovascular events in these patients, as well as with a greater risk of severe inflammation. Chronic inflammation contributes to the progression of renal disease, the pathogenesis of cardiovascular disease, and mortality. Moreover, clinically, the CKD-associated defect in the immune system also has a relevant impact on morbidity and mortality. Recent findings showing that excess FGF23 may affect non-traditional, off-target organs independently of αKlotho give support to the potential clinical relevance of the adverse effects of FGF23 in CKD, and even in non-CKD patients. In this review, we provide an update on FGF23 and briefly discuss its future in clinical practice